The Influence of Motivation, Communication, and Work Stress on Employee Job Satisfaction at PT BPR Berkah Pakto - Laksana, Ryan Galih Cahya; Meilina, Restin; Nurdiwaty, Diah (Universitas Nusantara PGRI Kediri, 2025)
Research Aim: This study aims to analyze the influence of motivation, communication, and work stress on job satisfaction among employees at BPR Berkah Pakto. The study also aims to provide recommendations to management regarding factors that can improve employee job satisfaction. Design/Method/Approach:This study uses a quantitative approach with a survey design. Data was collected by distributing questionnaires to 40 employees at BPR Berkah Pakto. The data were analyzed using multiple regression analysis with IBM SPSS software. Research Findings: The findings show that motivation, communication, and work stress significantly influence job satisfaction among employees at BPR Berkah Pakto. Among these three factors, communication has the strongest influence on job satisfaction. Theoretical Contribution/Originality: This study contributes to the development of motivation and communication theories within the context of small and medium-sized organizations. It also provides new insights into the impact of work stress on employee job satisfaction in the banking sector. Practical/Policy Implications: This study offers recommendations for BPR Berkah Pakto management to strengthen internal communication and give more attention to work stress management in order to improve employee job satisfaction. Research Limitation: This study is limited to a sample of employees at BPR Berkah Pakto, so the findings may not be generalizable to other organizations with different characteristics. Additionally, this study uses cross-sectional data and cannot demonstrate causal relationships.